A prospective study assessing the pattern of response of local disease at DCE-MRI after salvage radiotherapy for prostate cancer. (July 2022) - Bottero, Marta; Faiella, Adriana; Giannarelli, Diana; Farneti, Alessia; D'Urso, Pasqualina; Bertini, Luca; Landoni, Valeria; Vici, Patrizia; Sanguineti, Giuseppe
Highlights: Most local failures after radical prostatectomy dis-appears after dose escalated salvage radiotherapy. On average this takes approximately 5 months and almost 90% of lesions dis-appeared by 12 months from treatment. Larger lesions take longer to respond, with about 1/3 of lesions larger than 4.5 cc still detectable 1 year after treatment. Abstract: Background: To assess the pattern of response of presumed local lesions at dynamic contrast enhancement magnetic resonance imaging (DCE-MRI) after salvage radiotherapy (sRT). Methods: This is a prospective study conducted at a single Institution accruing patients with one or more local failures at DCE-MRI after radical prostatectomy between August 2017 and June 2020. Patients underwent exclusive sRT delivering 66–69 Gy and 73.5 Gy in 30 fractions to the whole prostatic fossa and to the local failure(s) seen at DCE-MRI, respectively. Patients were offered DCE-MRI at 3 months intervals after sRT until complete disappearance (CR) of the lesion(s) or up to a maximum of 4 revaluations. Results: 62 patients with 72 nodules were enrolled. All patients underwent the 1st revaluation, and 33 patients (53.2%) showed a CR. The median time to CR was 4.7 months. Four patients did not undergo further testing before achieving a CR and even considering these patients as no responses, the vast majority (87.1%, 95%CI: 78.5–94.4%) of lesions would have completely disappeared by 12 months from the end of sRT. The volume of the lesion at pre-sRT DCE-MRI was an independent predictor of CR at the 1st revaluation (OR: 0.076, 95%CI: 0.009–0.667; p = 0.020) along with time elapsed from sRT (OR: 3.399, 95% CI: 1.156–9.993, p = 0.026). Conclusions: The present study documents the complete disappearance of the vast majority of local lesions after dose-escalated sRT though this requires several months after sRT; timing of CR is at least in part predictable based on the volume of the lesion. Trial registration: Clinicaltrials.gov NCT04703543, registered July 15 2020, retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT04703543 .